Inulin-Type β2-1 Fructans have Some Effect on the Antibody Response to Seasonal Influenza Vaccination in Healthy Middle-Aged Humans - Lomax, Amy R.; Cheung, Lydia V. Y.; Noakes, Paul S.; Miles, Elizabeth A.; Calder, Philip C. (Frontiers in Immunology, 2015)
ß2-1 fructans are prebiotics and, as such, may modulate some aspects of immune function. Improved immune function could enhance the host’s ability to respond to infections. There is limited information on the effects of ß2-1 fructans on immune responses in humans. The objective of the study was to determine the effect of a specific combination of long-chain inulin and oligofructose (Orafti® Synergy1) on immune function in middle-aged humans, with the primary outcome being response to seasonal influenza vaccination. Healthy middle-aged humans (45 to 63 year of age) were randomly allocated to consume ß2-1 fructans in the form of Orafti® Synergy1 (8 g/day; n = 22) or maltodextrin as control (8 g/day; n = 21) for eight weeks. After four weeks participants received the 2008/2009 seasonal influenza vaccine. Blood and saliva samples were collected prior to vaccination and two and four weeks after vaccination. They were used to measure various immune parameters. The primary outcome was the serum concentration of anti-vaccine antibodies. Serum antibody titres against the vaccine and vaccine-specific immunoglobulin concentrations increased post-vaccination. Antibodies to the H3N2-like hemagglutinin type 3, neuraminidase type 2-like strain were higher in the Synergy1 group (P = 0.020 for overall effect of treatment group), as was serum vaccine-specific IgG1 two weeks post-vaccination (P = 0.028 versus control). There were no other differences between groups in antibody titres or anti-vaccine immunoglobulin concentrations, in blood immune cell phenotypes, or in a range of immune parameters. It is concluded that Orafti® Synergy1, a combination of b2-1 fructans, can enhance some aspects of the immune response in healthy middle-aged adults, but that this is not a global effect.